Pengaruh HbA1c Terhadap Profil Lipid pada Pasien Diabetes Melitus Tipe 2 - Suci, Maghfirly Juniarti Eka; Tjiptaningrum, Agustyas; Setiawan, Gigih; Kurniati, Intanri (CV. Jasa Sukses Abadi, 2024)
Diabetes Mellitus (DM) is characterized by a state of hyperglycemia due to insulin resistance, decreased insulin production, or both of these conditions which are classified into metabolic diseases. When checking the condition of type 2 DM, HbA1c can be checked as an indicator. High and uncontrolled HbA1c levels will cause disturbances in lipid profiles such as increased triglycerides, LDL, total cholesterol, and decreased HDL. The purpose of this study is to determine whether or not there is an effect of HbA1c on lipid profiles in type 2 DM patients. This method uses scientific publication search media such as Google Scholar, Pubmed, and old medical scientific journals using the keywords “lipid profile, HbA1c, type 2 diabetes mellitus, and dyslipidemia” obtained 15,700 articles and scientific journals. In patients with type 2 diabetes mellitus, glycemic control can be determined by HbA1c examination, high HbA1c levels are associated with disruption of lipid profile levels. The results of the study discuss the effect of HbA1c levels on lipid profiles in patients with type 2 diabetes and determine the relationship between the two.